Vers une ontologie de domaine pour l’analyse de l’état de conservation du bâti patrimonial - Tommy Messaoudi; sous la direction de Livio De Luca; Philippe Véron; Gilles Halin (In Situ)
The conservation and restoration of historic monuments require diagnostic analysis carried out by multidisciplinary teams. The elaboration of this diagnosis of a cultural heritage object involves direct observation, the examination of documentary sources and of diverse types of analytical data. While new tools now allow various experts to store and analyse their observations on different media, the data generated by these different actors is generally not linked to a unique reference, nor spatialized around it. Today, it is possible to generate dense and precise 3D models, but these spatial representations are not adequate for the requirements of real observations of conservation actors. This observation pinpoints the lack of operational frameworks for the capture of information pertaining to the analysis and interpretation of a state of conservation. The need to create a common analytical support is therefore central to these concerns. This is why the creation of an ontology in the field of conservation seems to be an innovative solution not only for making raw spatial representations intelligible, but also for introducing the notion of an informational continuum. By the interconnection of descriptors that are both qualitative (formalising shared knowledge) and quantitative, domain ontology constitutes the conceptual scaffolding which can help clarify all the interrelationships that, by combination, allow for a description of building degradation phenomena.